2022
DOI: 10.3390/su14127362
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Behavioural Biometrics for Continuous and Adaptive User Verification Using Smartphone and Smartwatch

Abstract: Recent studies have shown how motion-based biometrics can be used as a form of user authentication and identification without requiring any human cooperation. This category of behavioural biometrics deals with the features we learn in our life as a result of our interaction with the environment and nature. This modality is related to changes in human behaviour over time. The developments in these methods aim to amplify continuous authentication such as biometrics to protect their privacy on user devices. Vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…From our point of view, the use of non-commercial wearables makes it difficult to extrapolate the results to real applications, so we are interested in works that use smartwatches or smartbands to test our proposal, since these are the ones most closely related to our approach. From a review of the literature, the following works using commercial wearables were found: [ 18 , 19 , 20 , 21 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Related Workmentioning
confidence: 99%
“…From our point of view, the use of non-commercial wearables makes it difficult to extrapolate the results to real applications, so we are interested in works that use smartwatches or smartbands to test our proposal, since these are the ones most closely related to our approach. From a review of the literature, the following works using commercial wearables were found: [ 18 , 19 , 20 , 21 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Related Workmentioning
confidence: 99%
“…The authors discussed the balance between the number of dimensional features and the re-authentication time, which minimizes as the number of dimensions increases. Verma et al [25] proposed an algorithm to balance behavioral biometrics with multi-factor authentication by introducing a two-step user verification algorithm that verifies the user's identity using motion-based biometrics. Table 1 shows recent human activity datasets employed in the studies mentioned above.…”
Section: Related Workmentioning
confidence: 99%
“…Eight different activities MobiAct [19] 59 Nine different activities WISDM-HARB [21] 51 18 different tasks Hand Movement, Orientation and Grasp (HMOG) [22] 100 Six different activities [25] 5 1 4 3…”
Section: Related Workmentioning
confidence: 99%
“…Tere are several methods that use biometrics to approve the identity such as fngerprint [1], palm print [2], iris print [3], and voice print [4]. Biometrics include measuring an individual's distinctive physical or behavioral biometric trait [5]. Te Greek word "bio" means life and "metric" means measuring; both words are combined to form the phrase "biometric" [6].…”
Section: Introductionmentioning
confidence: 99%